(untitled) (Research, Society and Development, 2023)
The objective of this research was to correlate quality and marketed price of solid wood indicated for furniture in lumber companies in the municipality of Aracaju, SE, through roughness analysis. 15 establishments were selected, where only 33% sold solid wood, thus noting a low usability, compared to establishments that use wood panels, comprising about 54%. With the aid of a questionnaire for indication and data collection, the six most used species were selected, namely: Maracatiara, Maçaranduba, Angico, Imbira, Sucupira and Freijó, where it was possible to accurately analyze that there was no correlation between price and quality, indicating that it is possible to obtain parts with high surface quality, which is desired for furniture production, at a more affordable cost. Generating the need to do market analysis to seek more competitive prices, since there was significant variation between prices of the same species and between species, depending on the budgeted establishment. Due to the low correlation between quality and price, Imbira wood is indicated for the production of furniture, since it had the lowest market value.